Screening and identification of drought tolerance of spring soybean at seedling stage under climate change - Wang, Xin; Li, Xiaomei; Dong, Shoukun (Frontiers in Sustainable Food Systems, 2022)
Drought is one of the major abiotic stress factors limiting soybean growth and yield, and it frequently occur globally. Therefore, exploring resistant varieties from soybean germplasm is important under climate change. To screen drought resistant spring soybean varieties at seedling stage, pot experiment was used to detect the Survival percentage after drought stress of 60 soybean varieties at seedling stage, twice drought rehydration treatments on seedlings, to evaluate the drought tolerance of spring soybean. The results showed that at the seedling stage, 7 varieties were considered drought tolerant, 17 varieties were considered drought sensitive, and 36 varieties were considered to be moderately drought tolerant. Based on this experiment, number 44 (heinong37), 48 (heinong44), 49 (heinong45), 52 (heinong48) is considered the best drought resistant, and number 3 (dongnong48), 4 (dongnong52), 27 (suinong25), 60 (heinong65) is the most sensitive. These varieties provide a reference for further study on drought tolerance and stress resistance gene screening of soybean at the molecular level. The selected soybean varieties can be planted in areas with suitable climates and frequent drought to meet the local soybean demand. In other regions, although cannot be directly grown, they can still be used as parents of selected varieties or as materials for gene screening and extraction, to assist crop breeding at the molecular level in response to increasingly severe drought stress problems under the current climate trends.